Integrating Sports Coaching Expertise into Sports Entrepreneurship: A Strategic Model for Business Development - Sahabuddin, Sahabuddin; Lengkana, Anggi Setia; Sofyan, Davi (Universitas Majalengka, 2025)
This study explores the integration of sports coaching expertise into sports entrepreneurship as a strategic effort to promote business development in Makassar City. Despite the city’s rich sporting ecosystem, comprising over 150 registered clubs, 80 certified coaches, and a growing number of private training centres, the adoption of sportpreneurship remains underdeveloped. Using a qualitative descriptive design with an exploratory case study approach, data were collected from 50 informants, including experienced coaches, athlete-entrepreneurs, academics, sports business owners, and sports training institution managers. Methods included semi-structured in-depth interviews, focus group discussions (FGDs), document analysis, and participatory observation. Findings reveal that 84% of coaches recognize leadership and communication skills as highly transferable to entrepreneurial contexts, yet 62% cite regulatory and financial constraints as major obstacles. FGDs showed broad consensus on the need for structured mentorship and entrepreneurship education. Document analysis highlighted gaps in local policy and training curricula, while observational data confirmed inconsistent support for sportpreneur activities in practice. A strategic model was developed, consisting of four core components: coaching competencies, institutional support, education and mentorship, and partnership ecosystems. This model offers practical guidance for policymakers, educators, and sports organizations seeking to foster entrepreneurship within the coaching community. The study concludes that aligning coaching skills with entrepreneurial strategies can enhance individual career opportunities and support sustainable economic development in regional sports sectors. Recommendations include curriculum reform, targeted policy incentives, and public-private collaborations to operationalize the proposed model.